Efficacy of beetroot juice on reducing blood pressure in hypertensive adults with autosomal dominant polycystic kidney disease (BEET-PKD): study protocol for a double-blind, randomised, placebo-controlled trial - Sagar, Priyanka S.; Munt, Alexandra; Saravanabavan, Sayanthooran; Vahedi, Farnoosh Asghar; Elhindi, James; Nguyen, Beatrice; Chau, Katrina; Harris, David C.; Lee, Vincent; Sud, Kamal; Wong, Nikki; Rangan, Gopala K. (Current controlled trials in cardiovascular medicine, 2023)
In autosomal dominant polycystic kidney disease (ADPKD) impaired nitric oxide (NO) synthesis, in part, contributes to early-onset hypertension. Beetroot juice (BRJ) reduces blood pressure (BP) by increasing NO-mediated vasodilation. The aim of this double-blind, randomised, placebo-controlled study is to test the hypothesis that BRJ reduces systolic and diastolic clinic BP in hypertensive adults with ADPKD. Participants with ADPKD and treated hypertension (n = 60) will be randomly allocated (1:1) to receive a daily dose of either nitrate-replete (400 mg nitrate/day) or nitrate-deplete BRJ for 4 weeks. The co-primary outcomes are change in mean systolic and diastolic clinic BP before and after 4 weeks of treatment with daily BRJ. Secondary outcomes are changes in daily home BP, urinary albumin to creatinine ratio, serum and salivary nitrate/nitrite levels and serum asymmetric dimethylarginine levels before and after 4 weeks of BRJ. The effect of BRJ in ADPKD has not been previously tested. BRJ is an accessible, natural dietary supplement that, if effective, will provide a novel adjunctive approach for treating hypertension in ADPKD. ClinicalTrials.gov NCT05401409. Retrospectively registered on 27th May 2022.